GEC ESTRO ACROP consensus recommendations for contact brachytherapy for rectal cancer. (March 2022) - Stewart, Alexandra J.; Van Limbergen, Evert J.; Gerard, Jean-Pierre; Appelt, Ane L.; Verhaegen, Frank; Berbee, Maaike; Vuong, Te; Brooker, Ciarna; Rockall, Tim; Sun Myint, Arthur
Highlights: CXB appears to be an efficacious technique for rectal cancer treatment and may allow rectal preservation in selected patients. These GEC ESTRO ACROP recommendations recommend dose schemes in for rectal CXB. These recommendations advise reporting of tumour depth to enable future refinement of dose prescription and target definition. The routine collection and publication of outcome data including patient reported outcomes (PROs) is recommended. Abstract: Purpose: To issue consensus recommendations for contact X-Ray brachytherapy (CXB) for rectal cancer covering pre-treatment evaluation, treatment, dosimetric issues and follow-up. These recommendations cover CXB in the definitive and palliative setting. Methods: Members of GEC ESTRO with expertise in rectal CXB issued consensus-based recommendations for CXB based on literature review and clinical experience. Levels of evidence according to the Oxford Centre for Evidence based medicine guidance are presented where possible. Results: The GEC ESTRO ACROP consensus recommendations support the use of CXB to increase the chances of clinical complete remission and cure for patients who are elderly with high surgical risk, surgically unfit or refusing surgery. For palliative treatment, the use of CXB is recommended for symptomatic relief and disease control. The use of CXB in an organ-preservation setting in surgically fit patients is recommended within the setting of a clinical trial or registry. Conclusions: The GEC ESTRO ACROP recommendations for CXB are provided. Recommendations towards standardisation of reporting and prescription are given. Practitioners are encouraged to follow these recommendations and to develop further clinical trials to examine this treatment modality and increase the evidence base for its use. The routine collection of outcomes both clinical and patient-reported is also encouraged.